ТАЛАБАЛАРДА МАЪНАВИЙ ВА УМУМИНСОНИЙ ҚАДРИЯТЛАРГА НИСБАТАН МУНОСАБАТЛАРНИ РИВОЖЛАНТИРИШ - Аллияров, А.Д. (SCIENCE and SOCIETY, 2020)
The article provides an overview of the role of students in the development of effective organizational and pedagogical mechanisms based on national cultural and historical traditions, traditions and universal values, and the development of a methodological basis for deepening democratic reforms and developing civil society.